Acceptance and Rejection of Covid-19 Vaccine among Pregnant and Breast Feeding Women – a survey conducted in Outpatient Department of a tertiary care setup - Akhtar, Omema; Khan, Sarah; Shahnawaz, Shizra; Ismail, Shafaq; Khan, Saba; Yasmin, Haleema (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To ascertain the frequency of acceptance and rejection of covid-19 vaccination and the reasons behind their choices among pregnant and breast feeding women visiting outpatient department of a tertiary care setup. Methods: This cross-sectional study was conducted in the Department of Obstetrics and Gynaecology, Jinnah Postgraduate Medical Centre, Unit -1 for a period of one month. All women attending outpatient department during the study, fulfilling the inclusion criteria and willing to participate in the study were included after informed consent. A questionnaire designed to acquire general information about the study participant was filled by the researcher. Data was entered and analyzed using SPSS vr 21.0. Results: Out of 500 enrolled women, 249(49.8%) women were pregnant and 251(51.2%) were breast feeding. 171(34.2%) were vaccinated and 329(65.8%) were unvaccinated. There is a significant association between the concept regarding unavailability of significant data regarding safety during pregnancy and breast feeding or vaccine being harmful during pregnancy and breast-feeding for mother & baby and acceptance of vaccine (p-value < 0.001) Conclusion: Safety concerns regarding the vaccine for pregnant and breast-feeding mothers still hold them from getting vaccinated. Obstetricians and Gynaecologists of the country need to play a vital role in building up the confidence of this population over vaccination and should strongly recommend pregnant and breast feeding women following up in clinics to get vaccinated.